Bidirectional roles of neutrophil extracellular traps in oral microbiota carcinogenesis: A systematic review - Shen, Jie; Lin, Haitao; Mo, Kangnan; Liang, Zhong; Zhang, Yan; Quan, Huatao; Wang, Xing; Zhang, Chenping; Chen, Chao (Translational oncology, 2025)
•Elucidate the role of oral microorganisms in the development of oral squamous cell carcinoma.•Systematically elucidated the bidirectional role of neutrophil extracellular traps in oral microbiota carcinogenesis.•Explored the potential value of NETs as a biomarker in precancerous screening and prognostic diagnosis of oral squamous cell carcinoma. Neutrophil extracellular traps (NETs) are network structures composed of DNA, histones, and antimicrobial proteins,released by activated neutrophils to trap and eliminate extracellular pathogens. Recent research has demonstrated a strong correlation between NETs and various diseases, including immune dysregulation, thrombosis, and malignancies. This review synthesizes current research on NETs, focusing on its biological role in oral squamous cell carcinoma (OSCC) and explores its potential in treating. A literature review in the PubMed database was conducted to examine the impact of NETs on the homeostasis of oral microbiota and the involvement in the development of oral microbiota-related carcinogenesis. Various microorganisms, including Porphyromonas gingivalis, Fusobacterium nucleatum, Streptococcus spp., along with Candida albicans, as well as certain viruses such as Human papillomavirus (HPV), Human herpes virus 8 (HHV-8), and Herpes simplex virus-1 (HSV-1)are regulated by NETs during oral colonization and proliferation and have been identified as contributors to the pathogenesis of oral squamous cell carcinoma. NETs have been shown to play a dual role in the carcinogenic process of oral microbiota in humans. At the initial stage of tumor formation, NETs inhibit tumorigenesis by eliminating tumorigenic bacteria that infiltrated the tumor; however, following tumor establishment, various cytokines and chemokines that promote tumor progression are released by neutrophils during the NETs formation. This article reviews the oncogenic mechanisms of NETs in the oral microbiota, with potential implications for early tumor detection and the development of microbe-targeted therapies. [Display omitted]